Problem based learning for the teaching of probability in high school and categorization of errors presented by students - Sidney Leandro da Silva Viana; Claudia de Oliveira Lozada (Educação Matemática Debate, 2020)
In this paper we present a research whose objective was to verify the effectiveness of the active methodology of Learning Based on Problems in the teaching of Probability in High School, with a view to developing the competences and abilities foreseen in the Common National Curricular Base. For that, we proceeded to a qualitative research through a case study, applying a didactic sequence to a class of 2nd year High School students from a public school in Maceió (AL). In order to verify the effectiveness of the didactic sequence and the development of competences and skills provided for in the National Common Curricular Base, we created analysis tools to identify the types of errors and skills and competences developed. The results demonstrated the need for teachers to know the PBL to use it in classes, in addition to understanding that its application differs in several aspects from application in Higher Education, with the need to adapt it Basic Education.